PENGARUH STRES KERJA, KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION PADA KARYAWAN - Septia Ningsih, Ni Kadek Windi; Putra, Made Surya (E-Jurnal Manajemen, 2019)
This research was conducted at the Toya Devasya Natural Hot Spring & Camping Resort, located in puri bening road (STA), toya bungkah, kintamani, Bangli, Bali. The number of respondents in this study were 102 contract employees. Data collection in this study is by distributing questionnaires using a 5-point Likert scale to measure 16 indicators. The data analysis technique used is multiple linear regression analysis. Turnover intention is the desire of employees to withdraw from where they work. A high turnover intention will have a bad impact on the organization, therefore it must be considered several variables that affect turnover intention. This study aims to 1. Know the effect of work stress on turnover intention, 2. Know the effect of job satisfaction on turnover intention, 3. Know the effect of organizational commitment on turnover intention. Keywords : work stress, job satisfaction, organizational commitment, turnover intention